Ecofeminism and Urban Farming: Empowering Women Farmers in Serang City, Indonesia - Selvi Sulistiani; Ika Arinia Indriyany (Dealings Foundation Institute, 2025)
This articel analyzes the role of ecofeminism in the activism of Women Farmers' Groups in Serang City in shaping ecological spaces through empowerment-based urban farming. The urgency of this research is grounded in the persistent patriarchal culture that confines women to the domestic sphere, despite many being in their productive years. Empowerment through Women Farmers' Groups serves as a form of resistance by creating ecological spaces that enable women to become independent and self-sufficient without leaving their homes. This article is conducted in Serang City, where land conversion into residential areas has resulted in numerous idle lands that have the potential to be utilized for urban farming. Employing a feminist critical ethnographic approach, the study finds that urban farming within Women Farmers' Groups fosters environmental awareness based on ecofeminist principles. This process occurs through knowledge reproduction facilitated by socialization and training, contributing to both household food security and environmental conservation. However, the lack of government support has led to the unsustainability of some Women Farmers' Groups due to insufficient monitoring and assistance. The findings of this study are expected to serve as an evaluation tool for optimizing Women Farmers' Groups programs, ultimately strengthening food security and enhancing women's participation in environmental conservation through the creation of ecological spaces.